(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
Infantile hemangiomas (IHs) are common benign vascular tumors in infants, often requiring treatment to manage complications and improve cosmetic outcomes. Non-ablative lasers have emerged as a promising tool in the treatment of IHs. Unlike ablative lasers, which remove surface tissue, non-ablative lasers target deeper vascular structures, reducing the hemangioma’s size and visibility with minimal surface damage and scarring. This article explores the potential applications, advantages, challenges, and integration of non-ablative lasers in the comprehensive treatment of IHs, emphasizing their role as a minimally invasive and effective therapeutic option.